1986
DOI: 10.1002/ana.410200304
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical identification of HTLV‐III antigen in brains of patients with AIDS

Abstract: Human T-cell lymphotropic virus type III (HTLV-III) has been isolated from neural tissues and cerebrospinal fluid (CSF) of patients with neurological syndromes associated with the acquired immune deficiency syndrome (AIDS) and the virus may be directly involved in the pathogenesis of the syndromes. To detect HTLV-III antigen in neural tissues from patients with AIDS, immunoperoxidase studies using a goat anti-HTLV-III serum were performed on frozen tissue sections of brain, spinal cord, and nerve from 13 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(110 citation statements)
references
References 40 publications
2
107
0
1
Order By: Relevance
“…HIV-1 viral products can be released by infected microglia and astroglia (Ensoli et al, 1990;Munis et al, 1992;Robert-Guroff et al, 1990;Chang et al, 1997;Shutt and Soil, 1999;Jones et al, 1998;Jones et al, 2000), and can also induce the production and release of proinflammatory cytokines and cellular toxins in neural cells (Yeung et al, 1995;Adamson et al, 1996;Bagetta et al, 1996a;Kaul and Lipton, 1999;Nath et al, 1999). Numerous lines of evidence suggest that extracellular proinflammatory cytokines and cellular toxins can induce neuronal apoptosis (Gabuzda et al, 1986;Gendelman et al, 1994;Shi et al, 1998;New et al, 1998;Bagetta et al, 1999;Holden et al, 1999;Zheng et al, 1999;Park et al, 2001;Takahashi et al, 1996). Furthermore, several studies suggest that HIV-1 Tat and gp120 interact with neuronally-expressed receptors to activate multiple pro-apoptotic signaling cascades in neurons Moore et al, 1997;New et al, 1997;Shi et al, 1998;Piller et al, 1999;Bonavia et al, 2001;Corasaniti et al, 2001;Haughey et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 viral products can be released by infected microglia and astroglia (Ensoli et al, 1990;Munis et al, 1992;Robert-Guroff et al, 1990;Chang et al, 1997;Shutt and Soil, 1999;Jones et al, 1998;Jones et al, 2000), and can also induce the production and release of proinflammatory cytokines and cellular toxins in neural cells (Yeung et al, 1995;Adamson et al, 1996;Bagetta et al, 1996a;Kaul and Lipton, 1999;Nath et al, 1999). Numerous lines of evidence suggest that extracellular proinflammatory cytokines and cellular toxins can induce neuronal apoptosis (Gabuzda et al, 1986;Gendelman et al, 1994;Shi et al, 1998;New et al, 1998;Bagetta et al, 1999;Holden et al, 1999;Zheng et al, 1999;Park et al, 2001;Takahashi et al, 1996). Furthermore, several studies suggest that HIV-1 Tat and gp120 interact with neuronally-expressed receptors to activate multiple pro-apoptotic signaling cascades in neurons Moore et al, 1997;New et al, 1997;Shi et al, 1998;Piller et al, 1999;Bonavia et al, 2001;Corasaniti et al, 2001;Haughey et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The most characteristic feature of HIV-infected brain is that virus is concentrated in microglia and macrophages, with a very limited infection of astrocytes, endothelial cells, or neurons (Gabuzda et al, 1986;Wiley et al, 1986). Recent studies have suggested the model in which HIV entry into the CNS is mediated by circulating lymphocytes or monocytes, which in turn transmit virus to perivascular macrophages and microglia (Lane et al, 1996).…”
Section: Hivmentioning
confidence: 99%
“…The entry of human immunode®ciency virus (HIV-1) into the central nervous system (CNS) has been shown to occur early in the course of infection and to be associated with the development of neurological disorders, such as the acquired immunode®ciency syndrome (AIDS) dementia complex (Ho et al, 1985;Gabuzda et al, 1986;Resnick et al, 1988). The brain has also been identi®ed as a site of HIV-1 replication and as such may act as a reservoir for the virus, allowing the periphery to be re-infected (Black, 1985).…”
Section: Introductionmentioning
confidence: 99%